Adaptive Evolution of Extreme Acidophile Sulfobacillus thermosulfidooxidans Potentially Driven by Horizontal Gene Transfer and Gene Loss - Zhang, Xian (Appl Environ Microbiol, 2017)
Recent phylogenomic analysis has suggested that three strains isolated from different copper mine tailings around the world were taxonomically affiliated with Sulfobacillus thermosulfidooxidans. Here, we present a detailed investigation of their genomic features, particularly with respect to metabolic potentials and stress tolerance mechanisms. Comprehensive analysis of the Sulfobacillus genomes identified a core set of essential genes with specialized biological functions in the survival of acidophiles in their habitats, despite differences in their metabolic pathways. The Sulfobacillus strains also showed evidence for stress management, thereby enabling them to efficiently respond to harsh environments. Further analysis of metabolic profiles provided novel insights into the presence of genomic streamlining, highlighting the importance of gene loss as a main mechanism that potentially contributes to cellular economization. Another important evolutionary force, especially in larger genomes, is gene acquisition via horizontal gene transfer (HGT), which might play a crucial role in the recruitment of novel functionalities. Also, a successful integration of genes acquired from archaeal donors appears to be an effective way of enhancing the adaptive capacity to cope with environmental changes. Taken together, the findings of this study significantly expand the spectrum of HGT and genome reduction in shaping the evolutionary history of Sulfobacillus strains. IMPORTANCE Horizontal gene transfer (HGT) and gene loss are recognized as major driving forces that contribute to the adaptive evolution of microbial genomes, although their relative importance remains elusive. The findings of this study suggest that highly frequent gene turnovers within microorganisms via HGT were necessary to incur additional novel functionalities to increase the capacity of acidophiles to adapt to changing environments. Evidence also reveals a fascinating phenomenon of potential cross-kingdom HGT. Furthermore, genome streamlining may be a critical force in driving the evolution of microbial genomes. Taken together, this study provides insights into the importance of both HGT and gene loss in the evolution and diversification of bacterial genomes.